'We don't have any of those people here...' - Comfort, Jude; Freijah, Rita; Horner, Barbara; McManus, Alexandra; Lovelock, G.; Hunter, M. (Australian Federation of AIDS Organisations, 2010)
Most people ageing with HIV in Australia are, and will continue to be, gay men. For those who avoided disclosing their sexuality throughout their lives or who have limited disclosure to a small circle, the prospect of dealing with aged-care services can be daunting. For many older gay men diagnosed with HIV in the eighties or nineties, the concerns around disclosing sexuality are compounded by past experiences of stigma and discrimination due to their sexuality, with additional fears around disclosure of their HIV-positive status. The GRAI research outlined in this article raises important issues that must be addressed in planning for the diversity of the Australian population - planning that needs to acknowledge the issues faced by the Australian cohort of gay men ageing with HIV. (Eds.)